Targeting lipid metabolism reprogramming of immunocytes in response to the tumor microenvironment stressor: A potential approach for tumor therapy - Zhang, Ming; Wei, Tingju; Zhang, Xiaodan; Guo, Danfeng (Frontiers in Immunology, 2022)
The tumor microenvironment (TME) has become a major research focus in recent years. The TME differs from the normal extracellular environment in parameters such as nutrient supply, pH value, oxygen content, and metabolite abundance. Such changes may promote the initiation, growth, invasion, and metastasis of tumor cells, in addition to causing the malfunction of tumor-infiltrating immunocytes. As the neoplasm develops and nutrients become scarce, tumor cells transform their metabolic patterns by reprogramming glucose, lipid, and amino acid metabolism in response to various environmental stressors. Research on carcinoma metabolism reprogramming suggests that like tumor cells, immunocytes also switch their metabolic pathways, named “immunometabolism”, a phenomenon that has drawn increasing attention in the academic community. In this review, we focus on the recent progress in the study of lipid metabolism reprogramming in immunocytes within the TME and highlight the potential target molecules, pathways, and genes implicated. In addition, we discuss hypoxia, one of the vital altered components of the TME that partially contribute to the initiation of abnormal lipid metabolism in immune cells. Finally, we present the current immunotherapies that orchestrate a potent antitumor immune response by mediating the lipid metabolism of immunocytes, highlight the lipid metabolism reprogramming capacity of various immunocytes in the TME, and propose promising new strategies for use in cancer therapy.